Modern Treatment Methods of Kidney Structure and Chronic Pyelonephritis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This scientific article is devoted to a comprehensive analysis of the anatomical structure of the kidney and chronic pyelonephritis, a common kidney disease, from a medical point of view. It provides detailed information about the causes of the disease, its development processes, types of clinical course, diagnostic methods and modern medical treatment strategies. The main purpose of the article is to scientifically highlight current issues related to the early detection of kidney diseases, correct assessment of their course and selection of the most effective treatment methods.